2014
DOI: 10.4081/audiores.2014.80
|View full text |Cite
|
Sign up to set email alerts
|

Language Outcomes Using Hearing Aids in Children with Auditory Dys-Synchrony

Abstract: There is a considerable debate on the use of hearing aid in children with auditory dys-synchrony (AD). To current date there are no similar Studies which show the effect of acoustic amplification on outcomes on speech and language development in children with AD are found in the literature. Thus, in the present study three children diagnosed to have AD were recruited and subjected to hearing aid trial and fitting based on the late latency response thresholds. Ranging from 7 months to 41 months of intervention … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
0
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(14 citation statements)
references
References 12 publications
0
0
0
Order By: Relevance
“…There is no reported degree of hearing loss. Captions: CI: cochlear implant; ANSD: auditory neuropathy spectrum disorder; HA: hearing aid studied children with ANSD and moderate hearing loss 26,27 . This result emphasizes the importance of neonatal hearing screening programs, which involve both evoked otoacoustic emissions and brainstem auditory evoked potentials, because the combination of both tests will avoid errors, allowing to verify babies with possible findings compatible with auditory neuropathy spectrum disorder 4,28,29 .…”
Section: Boy Who Received Unilateral CImentioning
confidence: 99%
See 4 more Smart Citations
“…There is no reported degree of hearing loss. Captions: CI: cochlear implant; ANSD: auditory neuropathy spectrum disorder; HA: hearing aid studied children with ANSD and moderate hearing loss 26,27 . This result emphasizes the importance of neonatal hearing screening programs, which involve both evoked otoacoustic emissions and brainstem auditory evoked potentials, because the combination of both tests will avoid errors, allowing to verify babies with possible findings compatible with auditory neuropathy spectrum disorder 4,28,29 .…”
Section: Boy Who Received Unilateral CImentioning
confidence: 99%
“…Two studies showed that children who use hearing aids may present benefits in speech perception skills, with regard to auditory recognition and comprehension, when evaluating children with degrees of hearing loss that ranged from mild to severe 12,26 . However, another study, which evaluated the language development of children using hearing aids with moderate to severe hearing loss, found superior performance for participants with lower degree of hearing loss, stating that amplification can help in hearing, but is not enough to modify the neural coding pattern that is altered in the different degrees of hearing loss, especially in the severe degree 27 .…”
Section: Boy Who Received Unilateral CImentioning
confidence: 99%
See 3 more Smart Citations